Transformasi Pengabdian Masyarakat menjadi Strategi Pertahanan dalam Menjaga Stabilitas Pangan Nasional - Josefine Lika Kartika; Aris Sarjito; Edy Saptono (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
Food security is a key pillar of national stability and defense, yet various community service programs focusing on food often operate partially and are not strategically integrated. This research aims to analyze the potential and transformation model for community service programs to become an effective part of the national food defense strategy. Using a qualitative literature review method, this study collects and synthesizes data from various academic sources, reports, and policy documents. The findings indicate that transforming the role of community service from a charitable approach to a systematic empowerment movement can shift communities from passive objects to active subjects in maintaining food stability. This transformation is realized through the optimization of local resources, such as home gardens, and the adoption of adaptive agricultural technologies. However, its implementation is challenged by weak synergy between the government's top-down approach, the suboptimal role of academia, and community initiatives whose potential has not been fully realized. By implication, this study asserts the need for a collaborative governance model that integrates community-based initiatives into the national policy cycle, allowing public participation to be optimally empowered as the frontline of Indonesia's food defense system.